2006
DOI: 10.1161/01.res.0000225911.24228.9c
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Peptide That Interferes With the Chemical Regulation of Connexin43

Abstract: Abstract-The carboxyl-terminal domain of connexin43 (Cx43CT) is involved in various intra-and intermolecular interactions that regulate gap junctions. Here, we used phage display to identify novel peptidic sequences that bind Cx43CT and modify Cx43 regulation. We found that Cx43CT binds preferentially to peptides containing a sequence RXP, where X represents any amino acid and R and P correspond to the amino acids arginine and proline, respectively.A biased "RXP library" led to the identification of a peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 37 publications
4
59
0
Order By: Relevance
“…Reduces atrial defibrillation upon oral administration RXP-E Ser-Asp-Asp-Leu-Arg-Ser-Pro-Gln-Leu-His-AsnGlu-Glu-Glu-Ser-Ala-Val-Pro-Phe-Tyr-Ser-His-Ser-HisMet-Val-Arg-Arg-Lys-Pro-Arg-Asn-Pro-Arg Prevents acidification-induced uncoupling (Shibayama et al, 2006) CyRP-71…”
Section: N-3-(4-hydroxyphenyl)-propionyl-pro-hyp-gly-ala-gly-ohmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduces atrial defibrillation upon oral administration RXP-E Ser-Asp-Asp-Leu-Arg-Ser-Pro-Gln-Leu-His-AsnGlu-Glu-Glu-Ser-Ala-Val-Pro-Phe-Tyr-Ser-His-Ser-HisMet-Val-Arg-Arg-Lys-Pro-Arg-Asn-Pro-Arg Prevents acidification-induced uncoupling (Shibayama et al, 2006) CyRP-71…”
Section: N-3-(4-hydroxyphenyl)-propionyl-pro-hyp-gly-ala-gly-ohmentioning
confidence: 99%
“…Nuclear magnetic resonance data showed that RXP-E induced a shift in the resonance peaks of amino acids D376 to D379 and amino acids N343 to K346 of Cx43. The latter two amino acids are part of the a-helical domain of the carboxyterminal domain of Cx43 (Shibayama et al, 2006). These two amino acid stretches are involved in the pH-dependent dimerization of the carboxyterminal domain (Sorgen et al, 2004).…”
Section: Future Prospectives: Rxp-peptides As Antiarrhythmic Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a new class of pharmacophores (RXP-E) have been developed that binds the carboxyl terminal domain of Cx43 (Cx43CT) and prevents cardiac gap junction closure and action potential propagation block [329,330]. While these compounds do not alter Cx40 conductance, we postulate that enhanced Cx43 conductance will overcome the effect of disease causing mutations in Cx40 and furthermore will demonstrate the capacity of iPSC based disease models for drug-discovery.…”
Section: Previous Work To Replicate Cardiac Diseases Using Ipsc Cell mentioning
confidence: 99%
“…In 2006, Shibayama et al [143] identified by phage display a series of RXP peptides (sequence of arginine, any amino acid, proline) capable of binding to the CT of Cx43. One of these peptides, RXP-E, prevented heptanol-and acidosis-induced closure of Cx43 gap junction channels in transfected cells and neonatal cardiomyocytes via an significant prolongation of the single channel open time [143,144].…”
Section: The Rxp Peptidesmentioning
confidence: 99%